2022
DOI: 10.1111/ene.15504
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Guillain–Barré syndrome following SARS‐CoV‐2 immunization: Analysis of a nationwide registry of recipients of 81 million doses of seven vaccines

Abstract: Background and purpose Information on Guillain–Barré syndrome (GBS) as an adverse event following immunization (AEFI) against SARS‐CoV‐2 remains scarce. We aimed to report GBS incidence as an AEFI among adult (≥18 years) recipients of 81,842,426 doses of seven anti‐SARS‐CoV‐2 vaccines between December 24, 2020, and October 29, 2021, in Mexico. Methods Cases were retrospectively collected through passive epidemiological surveillance. The overall observed incidence was ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Based on this, they concluded that the presence of viral RNA in influenza vaccines was capable of activating the immune system, providing evidence for a possible role as a trigger for autoimmune diseases [ 10 ]. The temporal association to RNA or viral vector vaccines suggests the vaccine as a trigger in predisposed individuals as is the case for some neurological adverse effects such as optic neuritis and transverse myelitis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, they concluded that the presence of viral RNA in influenza vaccines was capable of activating the immune system, providing evidence for a possible role as a trigger for autoimmune diseases [ 10 ]. The temporal association to RNA or viral vector vaccines suggests the vaccine as a trigger in predisposed individuals as is the case for some neurological adverse effects such as optic neuritis and transverse myelitis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the total incidence of GBS after SARS-CoV-2 vaccination in our study is comparable to the numbers reported by García-Grimshaw and colleagues, where they observed an incidence of 1.19/1,000,000 doses. 41 Finally, we did not account for the differences between homologous and heterologous vaccination and the different immunogenicity and reactogenicity conveyed by each method. 42,43 In our study, only one case of GBS following SARS-CoV-2 vaccination presented after heterologous vaccination (received ChAdOx1-S/nCoV-19 for the rst dose and BNT162b2 for the second dose).…”
Section: Discussionmentioning
confidence: 99%
“…The current report confirms the favorable response of post-COVID-19 immunization to plasmapheresis, rather than IV methylprednisolone. Recent studies reported more frequent use of IVIG, with less frequent use of plasmapheresis and rare use of steroids [ 16 , 17 ]. Similar to thesis reports, plasmaphereses showed favorable outcome [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported more frequent use of IVIG, with less frequent use of plasmapheresis and rare use of steroids [ 16 , 17 ]. Similar to thesis reports, plasmaphereses showed favorable outcome [ 16 , 17 ]. Plasmapheresis was used as it is more affordable and available.…”
Section: Discussionmentioning
confidence: 99%